2014
DOI: 10.5603/cj.a2013.0150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carvedilol on silent anthracycline-induced cardiotoxicity assessed by strain imaging: A prospective randomized controlled study with six-month follow-up

Abstract: These results indicate that carvedilol has a protective effect against the cardiotoxicity induced by ANT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
75
3
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 27 publications
(28 reference statements)
4
75
3
5
Order By: Relevance
“…The most important finding in the present study was that early administration of carvedilol significantly preserved LV function and inhibited LV remodeling. Our findings strengthen previous work (Kalay et al, 2006;Elitok et al, 2014) and highlight that early administration is essential for protecting against DOX-induced cardiomyopathy. This finding has important preclinical relevance that can be extrapolated to the clinical setting: early provision of carvedilol for chemotherapy patients may be crucial to prevent cardiotoxicity, which in turn preserves heart function and inhibits LV remodeling.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The most important finding in the present study was that early administration of carvedilol significantly preserved LV function and inhibited LV remodeling. Our findings strengthen previous work (Kalay et al, 2006;Elitok et al, 2014) and highlight that early administration is essential for protecting against DOX-induced cardiomyopathy. This finding has important preclinical relevance that can be extrapolated to the clinical setting: early provision of carvedilol for chemotherapy patients may be crucial to prevent cardiotoxicity, which in turn preserves heart function and inhibits LV remodeling.…”
Section: Discussionsupporting
confidence: 80%
“…The benefit of carvedilol on preserving heart function has been extensively discussed by numerous clinical observational studies (Kalay et al, 2006;Elitok et al, 2014). The most important finding in the present study was that early administration of carvedilol significantly preserved LV function and inhibited LV remodeling.…”
Section: Discussionsupporting
confidence: 61%
“…It can be inferred that the control group was affected by anthracycline-induced cardiotoxicity while carvedilol had a strong cardioprotective effect on the case group. Elitok et al [21] studied 80 patients with breast cancer receiving doxorubicin and showed that LV basal septal and basal lateral systolic strains were significantly reduced in patients that were not treated with carvedilol, which is in line with the results of this study.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, ejection fraction is not a sensitive parameter with which to evaluate the cardiotoxicity of anthracyclines, and carvedilol did not have an effect on ejection fraction after the chemotherapy either. Elitok et al [21] showed that there is no difference between LVEF in patients who received carvedilol and those who did not. Mukai et al [22] reported that 5 cases of diagnosed anthracycline-induced cardiomyopathy treated by carvedilol had an improvement in LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…13 Our patient population was similar to those assessed in previous studies of cardiotoxicity in breast cancer patients, 14,15 suggesting that our data could be used to identify patients at high risk of developing CIC.…”
Section: Discussionmentioning
confidence: 49%